2012
DOI: 10.2527/jas.2011-4908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various doses of injected selenium on performance and physiological responses of sheep to heat load1

Abstract: The aim of the study was to determine the effects of various doses of injected Se on the physiological responses of sheep to heat load. Fifteen 9-mo-old Australian Merino wethers (mean BW = 27.2 ± 2.1 kg) were randomly assigned to 1 of 3 treatments: 0 (control), 0.5, and 5 mg of Se, which was administered as a subcutaneous sodium selenate injection (5 mg/mL Se) on d 1, 8, and 15 of exposure to heat stress. The animals were housed individually in an environmental chamber and exposed to high temperature from 070… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 42 publications
7
26
1
1
Order By: Relevance
“…Animals on a decreased plane of nutrition mobilize adipose tissue to compensate for energy insufficiency. This observation agrees with our previous sheep study (Mahjoubi et al, 2014) and other ovine reports (Sano et al, 1983;Sevi et al, 2001;Caroprese et al, 2012;Alhidary et al, 2012). Furthermore, the increased NEFA concentration in PFTN controls compared with HS animals replicates findings across species, as similar results have been reported in pigs (Pearce et al, 2013;Sanz Fernandez et al, 2015), steers (O'Brien et al, 2010), and lactating cattle (Wheelock et al, 2010;Baumgard et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Animals on a decreased plane of nutrition mobilize adipose tissue to compensate for energy insufficiency. This observation agrees with our previous sheep study (Mahjoubi et al, 2014) and other ovine reports (Sano et al, 1983;Sevi et al, 2001;Caroprese et al, 2012;Alhidary et al, 2012). Furthermore, the increased NEFA concentration in PFTN controls compared with HS animals replicates findings across species, as similar results have been reported in pigs (Pearce et al, 2013;Sanz Fernandez et al, 2015), steers (O'Brien et al, 2010), and lactating cattle (Wheelock et al, 2010;Baumgard et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…However, Juniper et al (2008) and Alhidary et al (2012) showed that dietary supplementation of Se did not affect (p>0.05) the haematological parameters of lambs and sheep, respectively. In line with our findings, the concentrations of Hb and PCV were also unaffected by the iodine supplementation in male goats (Rajendran et al, 2001).…”
Section: Resultsmentioning
confidence: 85%
“…The Se and vitamin E requirements of heat stressed sheep are largely unknown because existing recommendations (0.1 and 15 mg/d for Se and vitamin E, respectively; NRC, 1985) were estimated based on prevention of white muscle disease in sheep (McDowell, 1992). Therefore, the concentration of Se used in this study was up to 8 times the NRC (1985) recommendation and was calculated based on results obtained by Alhidary et al (2012) whereas the concentration of vitamin E used in the current study was recommended by Kott et al (1998). It is generally accepted that heat stress exerts adverse effects when the THI exceeds 78 (Fuquay, 1981).…”
Section: Discussionmentioning
confidence: 99%